Identification of Resistant Entries Against Charcoal Rot Caused by Macrophomina phaseolina in Maize (Zea mays L.) - Bhaskar, A. Vijaya; Usharani, G.; Sravani, D.; Manjulatha, G. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted from November, 2022 to February, 2023 (rabi season) and July, 2023 to October, 2023 (kharif season) respectively at the Agricultural Research Station, Karimnagar, Telangana State, India to identify resistant hybrids for charcoal rot disease in maize. 469 entries with check were screened in randomized block design by tooth pick method of inoculation. During rabi, 2022–23, out of screened 275 (274+1) lines, one hybrid KMH-42283 was found resistant, 24 lines viz., KML-79, KML-52, KML-54, KML-10, KML-75, KML-34, KML-72, KML-80, KML-29, KML-61, KML-1, KML-5, KMH-422730, KMH-422758, KMH-422752, KMH-422753, KMH-42229, KMH-422788, KMH-422777, KMH-42284, KMH-42247, KMH-422972, KMH-422838 and KMH-421353 were found moderately resistant, Kaveri-50 (Check) entry has recorded 8.10 disease scale and remaining lines were found moderately susceptible and susceptible to charcoal rot disease. During kharif, 2023, out of screened 193 lines, 33 lines viz., KML-95, KML-109, KML-5, KML-102, KML-107, KML-25, KML-65, KML-114, KML-118, KML-49, KMH-422302, KMH-422307, KMH-422475, KMH-422325, KMH-422333, KMH-422381, KMH-422382, KMH-422383, KMH-422384, KMH-422391, KMH-422397, KMH-422590, KMH-422480, KMH-422518, NK-7702, DHM-121, DKC-9178, DKC-9233, P-3401, P-3302, KNMH-131, PAC-751 elite and GK-3237 were identified as moderately resistant to charcoal rot disease, one line Kaveri-50 (check) was severely affected by charcoal rot with 8.20 disease rating and rated as susceptible during kharif, 2023.